1994
DOI: 10.1093/carcin/15.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of an organic and an inorganic form of selenium on a mammary carcinoma cell line

Abstract: The development of new compounds with greater cancer inhibitory activity and that are well tolerated continues to be a priority in chemoprevention research involving selenium. One compound, 1,-4-phenylene-bis(methylene)selenocyanate (p-XSC), is representative of a series of organoselenium compounds with these characteristics. In this study, the effects of p-XSC on a mouse mammary carcinoma cell line were compared to those of sodium selenite, which has been shown to be growth inhibitory. Treatment with p-XSC ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(44 citation statements)
references
References 5 publications
4
38
0
2
Order By: Relevance
“…Many studies have showed that the inhibition effect of the growth of cancer cells may indicate that Se plays an important role in exerting carcinostatic activity. 17,[29][30][31][32] Our study further shows that such an inhibition effect is dose-and timedependent. The growth of HepG2 cells was inhibited when they were exposed to Selenite (>5 μM) for more than 24 h or to Selenite (>10 μM) for more than 12 h.…”
Section: Discussionsupporting
confidence: 71%
“…Many studies have showed that the inhibition effect of the growth of cancer cells may indicate that Se plays an important role in exerting carcinostatic activity. 17,[29][30][31][32] Our study further shows that such an inhibition effect is dose-and timedependent. The growth of HepG2 cells was inhibited when they were exposed to Selenite (>5 μM) for more than 24 h or to Selenite (>10 μM) for more than 12 h.…”
Section: Discussionsupporting
confidence: 71%
“…The way in which selenium could suppress neoplasia is not clear at all. In vitro, selenium compounds produce direct anti-tumour effects, as demonstrated by tumour cell growth inhibition and apoptosis promotion [32]. A large portion of selenium is incorporated into glutathione peroxidase, which is known to reduce lipid peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Selenodiglutathion induziert DNA-Fragmente Wu et al 1995), die als charakteristisches Zeichen für Apoptose angesehen werden (Bicknell et al 1994;Oberhammer et al 1993). Die Induktion von Apoptose wurde für Selenit und Selenodiglutathion nachgewiesen (Forrest et al 1994;Lanfear et al 1994;Thompson et al 1994). In verschiedenen Zellinien wirkten Selenodiglutathion (Poirier und Milner 1983;Santoro und Milner 1991) � Natriumselenit (Medina und Oborn 1984;Thompson et al 1994) � Dimethylselenid (Poirier und Milner 1983) � Selenocystein (Batist et al 1986) nicht aber Selenat oder Selenomethionin (Yan et al 1991) wachstumshemmend.…”
Section: Wirkungsmechanismusunclassified